Toxicological Evaluation of Novel Cyclohexenone Derivative in an Animal Model through Histopathological and Biochemical Techniques - Muhammad Kamil; Arifa Fatima; Sami Ullah; Gowhar Ali; Rasool Khan; Naila Ismail; Mughal Qayum; Marius Irimie; Catalina Georgeta Dinu; Hanadi Talal Ahmedah; Maria Elena Cocuz (Toxics, 2021)
Toxicity studies were conducted to provide safety data of potential drug candidates by determining lethal and toxic doses. This study was designed for pre-clinical evaluation of novel cyclohexenone derivative with respect to the acute and sub-acute toxicity along with the diabetogenic potential. Acute and sub-acute toxicity were assessed after intraperitoneal (i.p) injection of the investigational compound through selected doses for 21 days. This was followed by assessment of isolated body organs (liver, kidney, heart and pancreas) via biochemical indicators and histopathological techniques. No signs of toxicity were revealed in the study of acute toxicity. Similarly, a sub-acute toxicity study showed no significant difference in biochemical indicators on 11th and 21st days between treated and control groups. However, in blood urea nitrogen (BUN) and random blood glucose/sugar (RBS) values, significant differences were recorded. Histopathological evaluation of liver, kidney, pancreas and heart tissues revealed mild to severe changes in the form of steatosis, inflammation, fibrosis, necrosis and myofibrillary damages on 11th and 21st days of treatment. In conclusion, the median lethal dose of the tested compound was expected to be greater than 500 mg/kg. No significant change occurred in selected biomarkers, except BUN and RBS levels, but a histopathological study showed moderate toxic effect on liver, kidney, pancreas and heart tissues by the cyclohexenone derivative.